2020
DOI: 10.1101/2020.05.02.072215
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Oral pyruvate prevents glaucomatous neurodegeneration

Abstract: Intraocular pressure-sensitive retinal ganglion cell degeneration is a hallmark of glaucoma, the leading cause of irreversible blindness. Converging evidence indicates that agerelated bioenergetic insufficiency increases the vulnerability of retinal ganglion cells to intraocular pressure. To investigate further, we used metabolomics and RNA-sequencing to examine early glaucoma in DBA/2J mice. We demonstrate an intraocular pressure-dependent decline in retinal pyruvate levels coupled to dysregulated glucose met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 39 publications
2
8
0
Order By: Relevance
“…In vitro, we have recently demonstrated that pyruvate rescues RGCs from both glucose deprivation-induced death and oxidative injury. (Williams et al, 2020) We have also shown that oral pyruvate supplementation has a robust neuroprotective effect in both the DBA/2J mouse and the laser-induced rat model of glaucoma. (Williams et al, 2020) Furthermore, pyruvate and nicotinamide exhibit neuroprotective synergy in the DBA/2J model.…”
Section: Pyruvatementioning
confidence: 76%
See 2 more Smart Citations
“…In vitro, we have recently demonstrated that pyruvate rescues RGCs from both glucose deprivation-induced death and oxidative injury. (Williams et al, 2020) We have also shown that oral pyruvate supplementation has a robust neuroprotective effect in both the DBA/2J mouse and the laser-induced rat model of glaucoma. (Williams et al, 2020) Furthermore, pyruvate and nicotinamide exhibit neuroprotective synergy in the DBA/2J model.…”
Section: Pyruvatementioning
confidence: 76%
“…(Williams et al, 2020) We have also shown that oral pyruvate supplementation has a robust neuroprotective effect in both the DBA/2J mouse and the laser-induced rat model of glaucoma. (Williams et al, 2020) Furthermore, pyruvate and nicotinamide exhibit neuroprotective synergy in the DBA/2J model. (Williams et al, 2020) 6.2.6 mTOR mTOR (mammalian target of rapamycin) is a serine/threonine protein kinase that has been shown to have roles in cell growth, development and survival, as well as in response to upstream events including growth factors, hormones, DNA damage and energy metabolites.…”
Section: Pyruvatementioning
confidence: 76%
See 1 more Smart Citation
“…Continued elucidation of the mechanisms of Wallerian degeneration has further demonstrated the role of NAD in axon survival. NAD decreases in damaged axons (33), while expression of the Wld S allele or viral overexpression/modified localization of NMNATs are protective, restoring NAD levels (5,(34)(35)(36)(37). Increased NAD appears to exhibit numerous functional local roles in this context, including providing sufficient substrate to mitigate local SARM1-dependent NAD consumption and protecting against nicotinamide mononucleotide (NMN) induced axon damage (38,39).…”
Section: Discussionmentioning
confidence: 99%
“…Its age-related depletion affects the biological coping mechanisms associated with inflammation, oxidative stress, and accumulation of damaged molecules [ 16 ]. All these alterations are intrinsically linked to retinal degenerative pathologies, such as glaucoma and AMD, and with compelling evidence that NAD + supplementation would be a promising intervention in these diseases [ 17 ], alone or possibly in combination with other nutraceutical agents such as saffron [ 18 , 19 ] and zeaxanthin [ 20 , 21 ], or pyruvate [ 22 ], which together provide neuroprotection by targeting multiple disease mechanisms. This review focuses on the shared pathophysiological mechanisms of glaucoma and AMD and the potential role that NAD + may play in their mitigation.…”
Section: Introductionmentioning
confidence: 99%